How do you solve -x^2+2x-1=0?

2 Answers
May 29, 2018

x=1

Explanation:

IT IS EASY!!
-x^2+2x-1=0 { * COMPARING WITH
ax^2+bx+c
we see
a=-1,b=2,c=-1
by splitting the middle term....
WE GET,
PRODUCT=ca = -1*-1=1
SUM = 2
*
therefore
-x^2+x+x-1=0
-x(x-1)+(x-1)=0
(-x+1)(x-1)=0
hence
x=1................................. hope u get it
* CHEERS !!:D *

May 29, 2018

x=1.

Explanation:

This equation can be solved by factorization.

-x^2 + 2x - 1 = 0

-1(x^2 -2x + 1) = 0

x^2 -2x + 1 = 0

x^2 - x - x + 1 =0

x( x-1 ) -1( x-1 ) =0

( x-1 )( x-1 ) = 0

Now,
x-1 = 0

Therefore, x=1.